2015
DOI: 10.1016/j.jped.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Peri-intraventricular hemorrhage and oxidative and inflammatory stress markers in very-low birth weight newborns

Abstract: ROI, GSH, and IL-6 levels were not associated with the occurrence of PIVH in very-low birth weight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
9
0
6
Order By: Relevance
“…These include glutathione [ 53 , 109 ], antioxidant vitamins [ 106 , 110 ], uric acid [ 111 ], ubiquinone-reducing substances [ 54 , 112 ], metallothionein [ 113 ], and thioredoxin system [ 114 , 115 ]. However, methods for the detection of oxidative stress related nonenzymatic antioxidants in the peripheral blood are few; one study on the level of glutathione (GSH) in umbilical cord blood after neonatal periventricular hemorrhage found that cord blood GSH level was not related to intraventricular hemorrhage in low-birthweight neonates [ 116 ]. Uric acid is an antioxidant molecule of the body, but studies have found that although serum uric acid levels are related to ischemic stroke, they have no significant correlation with ICH [ 111 ].…”
Section: Detection Of the Level Of Oxidative Stressmentioning
confidence: 99%
“…These include glutathione [ 53 , 109 ], antioxidant vitamins [ 106 , 110 ], uric acid [ 111 ], ubiquinone-reducing substances [ 54 , 112 ], metallothionein [ 113 ], and thioredoxin system [ 114 , 115 ]. However, methods for the detection of oxidative stress related nonenzymatic antioxidants in the peripheral blood are few; one study on the level of glutathione (GSH) in umbilical cord blood after neonatal periventricular hemorrhage found that cord blood GSH level was not related to intraventricular hemorrhage in low-birthweight neonates [ 116 ]. Uric acid is an antioxidant molecule of the body, but studies have found that although serum uric acid levels are related to ischemic stroke, they have no significant correlation with ICH [ 111 ].…”
Section: Detection Of the Level Of Oxidative Stressmentioning
confidence: 99%
“…In tissue injury process caused by oxidative stress, the lipid, protein and nucleic acid in cellular structure can react with oxygen free radicals, and these oxidized cell components will further cause cell dysfunction [21][22]. MDA, AOPP and 8-OHdG are the oxidation reaction products of lipid, protein and nucleic acid respectively, and can be used to evaluate the extent of the oxidative stress reaction after released into the blood circulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Caldas et al [8] studied IL-6 levels in umbilical cord blood of 125 infants with very low birth weight, while the incidence rate of IVH was assessed through cranial ultrasound scans. No statistically significant associations were found between IL-6 levels and IVH either.…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%
“…Association with increased risk of PHH, but not with WMI [27]. No association with increased risk of abnormal neurological outcome (including IVH) [34]IL-6Maternal vein blood serumNo association with increased risk of IVH [26]Umbilical cord bloodNo association with increased risk of IVH [7, 8, 10, 15, 30]Infant’s vein blood serumAssociation with increased risk of IVH, its severity, and higher neonatal morbidity [13]. Association with abnormalities in CUS only in infants born after or in week 28 of gestational age [34]Cerebrospinal fluidAssociation with increased risk of PHH, but not with WMI [27].…”
Section: Tumor Necrosis Factor (Tnf-alpha)mentioning
confidence: 99%